(untitled) (Research, Society and Development, 2024)
Healthcare-Related Infections are a serious public health problem, with Surgical Site Infections being the third most common post-operative complication. In Brazil, it accounts for around 17% of infections in patients undergoing surgical procedures. In developed countries, it can affect an average of 1/3 of surgical cases worldwide. Most of them are considered to be undesirable damage to health care, with preventable causes. Objective: To analyze in the scientific literature the strategies for the prevention and control of Surgical Site Infection carried out by the nursing team in hospitals. Methodology: This is an integrative review according to the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The time series was from 2018 to 2023 with the identification of 1,761 publications. After applying the eligibility criteria, 14 articles and 7 national and international guidelines were consolidated for analysis. Several studies highlight the role of nurses in conducting SSI prevention actions, either by executing the nursing process or by directing necessary interventions according to actual or potential problems presented by patients. It was noted that the adaptation and implementation of protocols, bundles, checklists and health education are fundamental strategies for standardizing and qualifying the care provided by the nursing team to surgical patients, as well as minimizing and reducing the rates of SSI. It is therefore necessary to strengthen research and development by continuously investing in new technologies, materials and surgical approaches that reduce the risk of SSI.